Investigating the Impact of Tropical Cyclones Cempaka and Dahlia on Atmospheric Conditions in Southern Indonesia - Vita, Tika Ayunda; Anggoro, Mochammad Donny; Aminuddin, Jamrud (Pusat Penelitian dan Pengembangan BMKG, 2025)
At the end of 2017, the Jakarta Tropical Cyclone Warning Center (TCWC) observed the formation of two tropical cyclones in the southern waters of Indonesia, namely Cempaka and Dahlia, which triggered extreme weather events and caused damage and casualties in several regions. This study aims to identify the developmental stages of tropical cyclones Cempaka and Dahlia, from formation to dissipation, and to examine atmospheric conditions before, during, and after the cyclones. The analysis employs the Dvorak technique based on Himawari-8 satellite infrared imagery to monitor cyclone intensity, supported by ECMWF reanalysis data to evaluate atmospheric parameters in the cyclone growth region. The results indicate that Cempaka and Dahlia reached the Tropical Storm (TS) category on 27 November and 1 December 2017, respectively. During the mature stage, atmospheric conditions were characterized by high relative humidity ranging from 90% to 100%, strong cyclonic circulation with negative vorticity values between −10 × 10⁻⁵ s⁻¹ and −50 × 10⁻⁵ s⁻¹, and lower-level convergence indicated by negative divergence values ranging from −10 × 10⁻⁵ s⁻¹ to −20 × 10⁻⁵ s⁻¹. These conditions support the development of convective clouds and the intensification of the cyclonic systems, providing insight into the role of atmospheric dynamics in the growth of tropical cyclones in the vicinity of Indonesia.